2009
DOI: 10.1128/iai.01256-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphatidylinositol Mannosides in the Interaction between Mycobacteria and DC-SIGN

Abstract: The C-type lectin dendritic cell (DC)-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN) is the major receptor on DCs for mycobacteria of the Mycobacterium tuberculosis complex. Recently, we have shown that although the mannose caps of the mycobacterial surface glycolipid lipoarabinomannan (ManLAM) are essential for the binding to DC-SIGN, genetic removal of these caps did not diminish the interaction of whole mycobacteria with DC-SIGN and DCs. Here we investigated the role of the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 74 publications
3
75
0
Order By: Relevance
“…Importantly, PIMs are also recognized by the C-type lectins mannose receptor, mannose-binding protein, and DC-SIGN and, as such, play a role in the opsonic and non-opsonic binding of M. tuberculosis to phagocytic and non-phagocytic cells. The higher forms of PIMs in particular, which contain two ␣-1,2-linked Manp residues, identical to the dimannoside motif decorating the nonreducing termini of the arabinosyl side chains of mannosylated LAM, have been shown to share with mannosylated LAM the ability to engage the mannose and DC-SIGN receptors of phagocytic cells and, in so doing, to impact phagosome-lysosome fusion in cultured human monocyte-derived macrophages (54,58). Both the fatty acyl appendages of PIMs and their degree of mannosylation are important to their interactions with host cells.…”
Section: Knowns and Unknowns Of The Physiological Roles And Biologicamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, PIMs are also recognized by the C-type lectins mannose receptor, mannose-binding protein, and DC-SIGN and, as such, play a role in the opsonic and non-opsonic binding of M. tuberculosis to phagocytic and non-phagocytic cells. The higher forms of PIMs in particular, which contain two ␣-1,2-linked Manp residues, identical to the dimannoside motif decorating the nonreducing termini of the arabinosyl side chains of mannosylated LAM, have been shown to share with mannosylated LAM the ability to engage the mannose and DC-SIGN receptors of phagocytic cells and, in so doing, to impact phagosome-lysosome fusion in cultured human monocyte-derived macrophages (54,58). Both the fatty acyl appendages of PIMs and their degree of mannosylation are important to their interactions with host cells.…”
Section: Knowns and Unknowns Of The Physiological Roles And Biologicamentioning
confidence: 99%
“…The regulatory mechanisms involved and the specific steps of the PIM pathway at which they act, whether exclusively at the level of LpqW or otherwise, are not known. Although higher order PIMs are dispensable molecules in M. smegmatis, M. bovis BCG, and M. tuberculosis (31,54), 4 such is not the case with PIM 1 and PIM 2 , the disruption of which causes immediate growth arrest in both fast-and slowgrowing mycobacteria (22,23). Interestingly, we found the disruption of the acyltransferase Rv2611c to be lethal to M. tuberculosis H37Rv and to result in severe growth defects in M. smegmatis (25), 4 emphasizing the critical physiological impact of not only the degree of mannosylation of PIMs but also their acylation state.…”
Section: Knowns and Unknowns Of The Physiological Roles And Biologicamentioning
confidence: 99%
“…The presence of multiple other MR and DC-SIGN ligands at the cell surface of Mtb , including glycoproteins (see Glycoproteins section), polar forms of PIMs (PIM 5 -PIM 6 ) and capsular polysaccharides (arabinomannan, mannan) (see Capsular Polysaccharides section) sharing with ManLAM terminal α–(1,2)-linked oligomannoside appendages, is thought to account for this absence of phenotype. Polar forms of PIMs in particular have been shown to participate in DC-SIGN binding (Torrelles et al ., 2006; Driessen et al ., 2009) and phagocytosis events through the MR limiting phagosome-lysosome fusion. In addition to C-type lectins, Mtb interacts with Toll-like receptors (TLR); LM and, to a lesser extent, ManLAM have been shown to be potent TLR-2 ligands (Nigou et al , 2008).…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%
“…The essentiality of much of the PIM/LM/LAM pathway for Mtb growth limits the number of informative isogenic mutants that can be generated for cellular and in vivo studies. Moreover, with the exception of one mutant dramatically affected in its cell envelope integrity (Fukuda et al ., 2013), the few Mtb PIM/LM/LAM recombinant strains that have constructed thus far failed to significant differ from their wild-type parent strain in terms of interactions with host cells, virulence or immunogenicity (Driessen et al ., 2009; Afonso-Barroso et al ., 2012). The presence of multiple glycoconjugates with partially overlapping activities at the surface of Mtb , the genetic diversity of Mtb isolates and the existence of regulatory mechanisms affecting the production of these compounds render the precise delineation of the roles of PIMs, LM and LAM in host-pathogen interactions extremely complex (Pitarque et al ., 2005; Appelmelk et al ., 2008; Driessen et al ., 2009; Torrelles and Schelsinger, 2010; Afonso-Barroso et al ., 2012).…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%
“…Given the developing popularity of "MOM" for the mycobacterial outer membrane, a related simple suggestion might be "MIM" for the "mycobacterial inner membrane". It was found that disruption of PIM 2 production causes growth arrest [67,68] but the higher PIMs were dispensable [69], thereby indicating an important structural role for PIM 2 . It has also been indicated that the acylation state of PIMs is also significant [70].…”
Section: Cell Envelope Organisationmentioning
confidence: 99%